Diasporas - Beine, Michel; Docquier, Frederic; Ozden, Caglar (2012)
Migration flows are shaped by a complex combination of self-selection and out-selection mechanisms. In this paper, the authors analyze how existing diasporas (the stock of people born in a country and living in another one) affect the size and human-capital structure of current migration flows. The analysis exploits a bilateral data set on international migration by educational attainment from 195 countries to 30 developed countries in 1990 and 2000. Based on simple micro-foundations and controlling for various determinants of migration, the analysis finds that diasporas increase migration flows, lower the average educational level and lead to higher concentration of low-skill migrants. Interestingly, diasporas explain the majority of the variability of migration flows and selection. This suggests that, without changing the generosity of family reunion programs, education-based selection rules are likely to have a moderate impact. The results are highly robust to the econometric techniques, accounting for the large proportion of zeros and endogeneity problems.